Comparison of the Financial Performance of Amil Zakat Agencies in Indonesia and Malaysia Using International Standard of Zakat Management (ISZM) - Hasanah, Lailatul; Sudaryono (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Optimal management of zakat funds is able to affect public trust in providing zakat funds to zakat institutions, this can be proven in research that accountability and transparency in financial reporting have a significant influence on the financial performance of zakat fund receipts. This study was conducted with the aim of making a comparative analysis of the financial performance of the Amil Zakat Agency in Indonesia and Malaysia using the International Standard of Zakat Management (ISZM). The samples in this study were selected through the purposive sampling method. The assessment of the financial performance of the Amil Zakat Agency uses efficiency variables and capacity variables. The analysis tool in this study is an independent sample difference test t-test. The results of the study show that based on the program load ratio and the operational load ratio of the Amil Zakat Agency in Malaysia is better and more efficient than the Amil Zakat Agency in Indonesia, while based on the main revenue growth ratio and the program load growth ratio of the Amil Zakat Agency in Indonesia is better than the Amil Zakat Agency in Malaysia. The results of the independent t-test sample showed that there was a significant difference in the comparison of the financial performance of the Amil Zakat Agency in Indonesia and Malaysia in the program load ratio, operational expense ratio and main revenue growth ratio. Meanwhile, in the growth ratio of program expenses, there is no significant difference.